The Effect of Cone Drill Training on Running Speed Among Athletes at the Education and Guidance (D&B) Tutoring Center in Bengkulu City - Syufian Soleh Iman Yusuf; Dolly Apriansyah; Oetari Lismana (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study was motivated by the importance of improving athletes’ running speed as one of the key components in track and field. One form of training that can be used to improve running speed is the cone drill. This study aims to determine the effect of cone drill training on improving the 100-meter running speed of athletes from the Didikan dan Bimbingan (D&B) Training Center in Bengkulu City. The theoretical review in this study covers the concepts of physical training, cone drill exercises, and running speed theory in track and field. This study employed an experimental method using a one-group pre-test post-test design. The study population consisted of all athletes from the Bimbel Didikan dan Bimbingan (D&B) program in Bengkulu City, with a sample of 20 athletes comprising 15 male athletes and 5 female athletes. Data collection techniques were conducted through observation, documentation, and a 100-meter sprint test using a stopwatch as the research instrument. The cone drill training program was conducted for 5 weeks with a training frequency of 3 times a week. Data analysis techniques used descriptive statistics, the Liliefors normality test, and hypothesis testing using the t-test. The results of the study showed that the average pre-test time was 13.81 seconds and the post-test time was 13.05 seconds, representing an improvement of 0.79 seconds. The results of the hypothesis test showed a calculated t-value of 24.42, which is greater than the critical t-value of 2.093 at a significance level of 0.05. Thus, it can be concluded that the cone drill exercise has a significant effect on improving the 100-meter running speed of athletes from the Didikan dan Bimbingan (D&B) Bimbel in Bengkulu City.